ANALISIS DESAIN PEMBANGUNAN PLTS TERAPUNG DI DANAU TOBA: STUDI PADA ASPEK TEKNIK, EKONOMI, DAN LINGKUNGAN - Nainggolan, William Sutan; Wibawa, Unggul; Wijono, n/a (Jurnal Mahasiswa TEUB, 2024)
High level of solar radiation throughout the year makes solar photovoltaic systems (PV) as one of the options for clean energysources in Indonesia. Indonesia possesses significant potential for utilizing floating solar plants, given its 3.091 water resources. Lake Toba, situated in the North Sumatra province, stands as Indonesia's largest lake, covering an expansive area of 1.145 km2. With solar irradiation levels reaching 1757,1 kWh/m2/yr, the lake presents promising potential as a suitable location for floating solar plant installations. The study focused on the technical design of floating solar power plants, covering electrical components and civil structures like floaters, anchors, and moorings. Two scenarios were analyzed to determine plant capacity: maximum water surface area and peak load data of North Sumatra. Inverter capacity was restricted by a ratio of 1,15 to 1,25. Graphical simulations using Matlab software were conducted to assess PV module generation characteristics at various solar radiation levels. Economic analysis included Cost of Energy, Net Present Value, Profitability Index, and Payback Period over a 30-year project lifetime. Environmental analysis addressed GHG emissions reduction assuming a 1% yearly power depreciation. This study outlines the technical design for the Lake Toba floating solar plant with a capacity of 583 MWp covering 3,57 km2 water surface. The plant uses 988.080 PV modules 590 Wp and 48 inverters 10.000 kW, mounted on HDPE floaters with a taut mooring system. Estimated energy production stands at 854 GWh/year. Economic analysis reveals a positive NPV of Rp 5.8 trillion, PI exceeding 1 at 1.774, and a Payback Period of 9 years and 9 months, demonstrating the feasibility of constructing the 583 MW Lake Toba Floating Solar Plant. Environmental analysis indicates a reduction in GHG emissions on Sumatra Island by 18.68 kilotons of CO2 over the project's lifetime. Keywords: floating solar plant, renewable energy, economic analysis, environment analysis, Lake Toba